On the plasma-assisted modifications of pre-textured surfaces: shallow depth nitriding in cast iron, topography and instrumented sclerometry test response. - Santos Filho, Dinecio dos (2019)
A concept of plasma treatment for enhancing pre-textured surfaces of components made in pearlitic gray cast iron is proposed. It consists of a plasma nitriding at low temperatures and short times, in order to increase the hardness of the surface by means of a shallow depth nitride formation in the surface of the iron. As a result, the roughness pattern of a previously textured surface is preserved after the treatment. A review on the wear of internal combustion engine cylinders along with background research was conducted, which consisted in the description of cylinder bore wear features observed experimentally. The background research substantiated the significance of initiatives to enhance wear and friction response of pre-textured surfaces made of cast iron, such as the internal combustion engine cylinders. A series of plasma nitriding experiments was run on specimens extracted from engine cylinders. Flat specimens, obtained from blanks extracted from the cylinder wall of an engine cylinder block, were textured in laboratory in order to emulate the typical roughness distribution of an ordinary cylinder bore plateau honing process. Complementarily, a case-study experiment was performed in a honed sample of an internal combustion engine cylinder, whose surface in its original form (cylindrical) has been textured through industrial honing operations. Therefore, one among the potential applications of the research has been assessed. 3-D interference roughness measurements were performed before and after the plasma treatment to assess topographic stability of the textured surfaces. epsilon-Iron nitride (Fe3N) formation was identified via X-ray diffraction analysis. In addition, nitrogen concentration profile was quantitatively evaluated using wavelength-dispersive (X-ray) spectroscopy microanalysis, substantiating the nitride formation at shallow depth. Microhardness measurements and instrumented linear sclerometry test (\'scratch test\') results indicated that epsilon-iron nitride formation and solid solution hardening could provide enhanced properties to the surface of general pearlitic cast iron components, such as increase of wear resistance, and decrease of apparent coefficient of friction, in the assessed conditions. The results demonstrated that the roughness texture pattern was satisfactorily preserved after the treatment, which was supported by direct observation of the surfaces via scanning electronic microscopy.